Tourist perceptions of kuala terengganu as an islamic tourism destination - Muhammad Rafiq Fahmi Abd Rahman; Muhammad Shafiq Adam Shamsulazwadi; Muhammad Shahrul Nizam Iskandar Md Noor; Muhammad Syamil Afiq Azaham (2023)
This study is about tourists perception who visit Kuala Terengganu as an Islamic tourism destination . Perception is one of the important factors considered by tourist in visiting a destination beside motivation attractiveness, spiritual experience , culture attribute, religion and accessibility. Therefore, this research is to examine the relationship between brand image and tourist perceptions of Kuala Terengganu as an Islamic Tourism destination. Second, to examine the relationship between spiritual experience and tourist perceptions of Kuala Terengganu as an Islamic tourism destination. Lastly, to examine the relationship between cultural attributes and tourist perceptions of Kuala Terengganu as an Islamic tourism destination. The quantitative method used in this research is questionnaires. About 327 respondents which is domestic and international tourists who went and experience in Kuala Terengganu chosen in this study. Keywords: Tourist Perception, Islamic Tourism